Pengaruh Corporate Social Responsibility terhadap Financial Performance, Financial Stability, dan Financial Inclusion pada Perusahaan Sub-Sektor Perbankan di Indonesia - Firly Adrian Pratama; Tantina Haryati (Haka Vyza Media, 2026)
The quantitative research aims to analyze the impact of Corporate Social Responsibility (CSR) on three key banking indicators: financial performance, financial stability, and financial inclusion. Purposive sampling method, selected 32 banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period as samples, with the primary criterion being the publication of CSR reports within their annual reports. The data was processed using panel data regression analysis techniques with EViews 13. The study concludes that Corporate Social Responsibility (CSR) has a significant influence on financial performance, but has not been able to prove its impact on financial stability and financial inclusion in the banking sector.